Exhibit highlighting Colorado State University Libraries Archives and Special Collections: Special Collections - McClelland, Deborah Ann, artist; Colorado State University. Archives and Special Collections, author (Colorado State University. Libraries, 2018)
Display items from the third of four exhibit cases featuring Colorado State University Libraries' Archives and Special Collections. Focusing on Special Collections, included are illustrations from the D.K. Bailey collection of 19th century botany. A summary is given about the collection's volumes which include Pinetum Woburnense, Silva of North America, and Arboretum et Fruticetum Britannicum.
Special Collections: exhibit highlighting Colorado State University Libraries Archives and Special Collections
Keywords: Loudon, J. C. (John Claudius), 1783-1843; Forbes, James, 1773-1861; Faxon, Charles Edward, 1846-1918; Sargent, Charles Sprague, 1841-1927; Exhibitions; Botany; Drawings; Scientific illustration